Multi-Criteria Combined Forecasts - Kaźmierska-Zatoń, Maria; Zatoń, Wojciech (Wielokryterialne prognozy kombinowane, 2010)
Using combination of forecasts results from the underlying belief that there is no such a single model that could comprise the whole actual and often complex economic process. The aim of this paper is an attempt to look at combining forecasts as a multi-criteria decision-making process. It is a multi-criteria process as we need to select: (a) individual component forecasts (quantity, quality, type), (b) values of their weights (objective determination of weights or their arbitrary choice), (c) a mathematical representation of combination and (d) a measure to assess the quality of a combined forecast. In the paper we provide an overview of methods applied for combining forecasts and show the results of our study of a combined forecast for inflation in Poland. The analysis indicates that combining forecasts is fully justified, especially if weights for individual forecasts are determined on the basis of multi-criteria optimization. The results also show that combining forecasts is useful even if a dominant individual forecast exists.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 59-75
Keywords: forecast; combining; weights; criteria; optimization